Influence of Financial and Career Motivational Factors on Job Satisfaction among Academic Staff of Public Universities in South-East Nigeria - Iduozee, Imade; Dania, Omoyebagbe R. (NIU Journal of Management Sciences; Vol 12 No 2 (2026): NIU Journal of Management Sciences, Vol. 12, No. 2, June 2026, 2026)
This study investigated the influence of financial and career motivational factors on job satisfaction among academic staff of public universities in South-East Nigeria. Specifically, the study examined the influence of salary, promotion, and recognition on the job satisfaction of academic staff in public universities within the region. The study adopted a correlational survey research design. The population comprised 9,791 academic staff drawn from the ten public universities in the South-East geopolitical zone of Nigeria. A sample size of 400 respondents was determined using the Yamane (1967) sample size determination formula. Data were collected through a structured questionnaire and analyzed using descriptive statistics, including frequency distribution, mean, and standard deviation. Multivariate regression analysis was employed to test the influence of the independent variables (salary, promotion, and recognition) on the dependent variable (job satisfaction). The findings revealed that salary, promotion, and recognition significantly influence the job satisfaction of academic staff in public universities in South-East Nigeria at the 0.05 level of significance. The results indicate that improvements in financial rewards and career advancement opportunities are associated with higher levels of job satisfaction among university lecturers. Based on the findings, the study recommends that government and university management should review the salary structure and welfare packages of academic staff to ensure that they are equitable and commensurate with their contributions to the university system. Additionally, university authorities should prioritise timely staff promotions and institutionalize formal recognition programmes to acknowledge and reward outstanding performance among academic staff. These measures are expected to enhance job satisfaction, improve staff morale, and contribute to greater productivity and effectiveness within the university system. Keywords: Financial motivation, career motivation, salary, promotion, recognition, job satisfaction, academic staff, public universities, South-East Nigeria.